2021
DOI: 10.3390/plants10061242
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Salicylic Acid Improves Water Stress Tolerance in Conocarpus erectus L. and Populus deltoides L. Saplings: Evidence from Morphological, Physiological, and Biochemical Changes

Abstract: Reforestation efforts are being challenged as water stress is hampering the sapling growth and survival in arid to semiarid regions. A controlled experiment was conducted to evaluate the effect of foliar application of salicylic acid (SA) on water stress tolerance of Conocarpus erectus and Populus deltoides. Saplings were watered at 90%, 60%, and 30% of field capacity (FC), and half of the saplings under 60% and 30% FC were sprayed with 1.0 mM SA. Results indicated that dry weight production decreased signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 72 publications
18
14
0
Order By: Relevance
“…Currently, SA has been suggested as an important molecule involved in ameliorating plant drought stress [ 38 , 39 , 40 , 63 ]. However, the physiological and biochemical mechanisms involved on drought stress tolerance induced by SA in plants have not been well understood [ 42 , 43 ]. Some reports have shown that SA improves SOD and APX activities and leaf gas exchange in Conocarpus erectus , Populus deltoids, and Olea europaea plants subjected to drought stress [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, SA has been suggested as an important molecule involved in ameliorating plant drought stress [ 38 , 39 , 40 , 63 ]. However, the physiological and biochemical mechanisms involved on drought stress tolerance induced by SA in plants have not been well understood [ 42 , 43 ]. Some reports have shown that SA improves SOD and APX activities and leaf gas exchange in Conocarpus erectus , Populus deltoids, and Olea europaea plants subjected to drought stress [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological and biochemical mechanisms involved on drought stress tolerance induced by SA in plants have not been well understood [ 42 , 43 ]. Some reports have shown that SA improves SOD and APX activities and leaf gas exchange in Conocarpus erectus , Populus deltoids, and Olea europaea plants subjected to drought stress [ 38 , 42 ]. Therefore, we hypothesized that SA application triggers enzymatic and non-enzymatic antioxidant mechanisms, ameliorating oxidative stress and improving photosynthesis performance and plant growth in A. chilensis plants subjected to drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Asensio et al [ 27 ] reported that the exogenous application of JA resulted in an improvement in CO 2 uptake in drought-exposed Zoysia japonica plants. In addition, exogenous JA application has also been reported to increase the antioxidant mechanism and reduce the level of lipid peroxidation in drought-stressed maize plants [ 28 ]. Therefore, JA application can enhance the growth and development of plants by providing protection against biotic and abiotic stress [ 29 ].…”
Section: Introductionmentioning
confidence: 99%